Determination of Welding Velocity and Arc Energy for Fusion MAG Welding Joint - Abed-Alkareem, Salah Sabeeh (Al-Khwarizmi Engineering Journal, 2017)
Abstract This paper is an experimental work to determinate the effect of welding velocity and formed arc energy for CO2-MAG fusion weld pool. The input parameters (arc voltage, wire feed speed and gas flow rate) were investigated to find their effects on the weld joint efficiency. Design of experiment with response surface methodology technique was used to build empirical mathematical models for welding velocity and arc energy in term of the input welding parameters. The predicted quadratic models were statistically checked for adequacy purpose by ANOVA analysis. Additionally, numerical optimization was conducted to obtain the optimum values for welding velocity and arc energy. A good agreement was found between experimental and predicted results.